MIXED CODE IN NOVEL HANUM DAN RANGGA FAITH & THE CITY HANUM SALSABILA RAIS WORKS - Agus Sulaeman; Abdul Rohim (STIBA IEC JAKARTA, 2019)
The purpose of this study is to describe the code mixing in the novel Hanum and Rangga faith & the city by Hanum Salsabila Rais. In this study, researchers used qualitative research with content analysis research method (content analysis), in qualitative research of language and literature, researchers used documentation for the technique of collecting data because the data is novel by Hanum & Rangga. From the results of the research obtained that one kind of code mixing is idiom. In the novels